Basis risk, social comparison, perceptions of fairness, and demand for insurance: A field experiment in Ethiopia - Kramer, Berber; Porter, Maria; Wassie, Solomon B. (Wiley, 2026)
Index insurance lowers agricultural risk but covers only covariate risks. Since farmers do not have complete insurance, they may develop mistrust of insurance when experiencing crop losses and not receiving payouts. Although recent innovations in remote sensing enable the provision of more complete insurance including coverage for idiosyncratic risks, such insurance introduces differences in payouts within social networks, which might be considered unfair, introduce jealousy, and depress insurance demand. We conduct a lab-in-the-field experiment with farmers in Ethiopia to examine whether providing complete insurance coverage affects perceived fairness and insurance demand. We also examine effects of informing farmers about neighbors' payout experiences. We find that such social comparison increases perceived fairness of index insurance. Providing complete crop insurance increases perceived fairness of outcomes and willingness to pay for insurance, without introducing jealousy over neighbors receiving different payouts. These results are concentrated among men and those with little insurance knowledge.